ANALISIS DISPARITAS PENDAPATAN PEDAGANG MAKANAN GEROBAK DORONG ANTAR KECAMATAN DI KOTA DENPASAR - Dwi Setyadhi Mustika Made (Puslit Kependudukan dan Pengembangan SDM Universitas Udayana, 2013)
The mobility of labor in informal sector is considerably high, that causes the labor force becoming easy to get into the sector so it is expected to be a platform between job opportunity and the unemployment. That phenomenon can be seen through the job opportunity that widely open as formal sector labor in Denpasar, especially which operates in traded sector. Most of the traders in informal sector run their business by building the “warung tenda”, and also by using the “gerobak dorong”. Location usually becomes a consideration in operating their business. The location which is a center of public activity becomes their main option, because the chance to earn money is greater. This study generally aims to determine the characteristic of food trader “gerobak dorong” in 4 (four) subdistricts in Denpasar. This study also aims to determine whether the income disparity exists in food trader “gerobak dorong” among the subdistricts in Denpasar. The result is expected to be a reference in informal sector making policy in Denpasar. In total of 100 respondents, most of food traders “gerobak dorong” are in range of age 35 to 44 years old (35 percent). In amount of 68 percent of the traders are from East Java, and 33 percent new respondents have been operating the business less than 5 years. The result of the analisys which is conducted by using Kruskall-Wallis method suggests that the average of income disparity of food trader “gerobak dorong” in four subdistricts in Denpasar is different. It is in line with the statement of this research background that says different location results in different income. Location determines their success in trading. The location which is a center of public activity becomes their main option, because the chance to earn money is greater.